2019
DOI: 10.14283/jfa.2019.37
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Lifestyle Behaviors on the Incidence of Frailty

Abstract: Background: Frailty is a clinical state defined as an increase in an individual’s vulnerability to developing adverse health-related outcomes. Objectives: We propose that healthy behaviors could lower the incidence of frailty. The aim is to describe the association between healthy behaviors (physical activity, vaccination, tobacco use, and cancer screening) and the incidence of frailty. Design: This is a secondary longitudinal analysis of the Mexican Health and Aging Study (MHAS) cohort. Setting: MHAS is a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Yu et al [ 30 ] reported the studies from three prospective cohorts in Hong Kong, Taiwan-urban and Taiwan-rural, so we divided this study into three cohorts for meta-analysis; Yuki et al [ 28 ] evaluated the relationship between three dimensions of physical activity (daily number of walking steps, time of light-intensity physical activity, and time of moderate-to-vigorous intensity physical activity) and frailty risk among Japanese, and therefore we divided it into three records when doing meta-analysis. Among the other eight included studies, two studies were from Finland [ 21 , 27 ], two from the UK [ 26 , 29 ], one from Japan [ 25 ], one from the USA [ 24 ], one from Mexico [ 20 ], and one from Spain [ 19 ]. A total of 34,943 participants were included in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yu et al [ 30 ] reported the studies from three prospective cohorts in Hong Kong, Taiwan-urban and Taiwan-rural, so we divided this study into three cohorts for meta-analysis; Yuki et al [ 28 ] evaluated the relationship between three dimensions of physical activity (daily number of walking steps, time of light-intensity physical activity, and time of moderate-to-vigorous intensity physical activity) and frailty risk among Japanese, and therefore we divided it into three records when doing meta-analysis. Among the other eight included studies, two studies were from Finland [ 21 , 27 ], two from the UK [ 26 , 29 ], one from Japan [ 25 ], one from the USA [ 24 ], one from Mexico [ 20 ], and one from Spain [ 19 ]. A total of 34,943 participants were included in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…However, epidemiological studies on the relationship between PA and frailty did not reach to a consistent conclusion. For instance, Trombetti [ 18 ] and Pérez-Tasigchana [ 19 ] did not find any association between PA and frailty, while Borda [ 20 ] and Savela [ 21 ] reported that PA was a protective factor for frailty. A meta-analysis found that physical exercise therapy could improve mobility and physical functioning in elderly patients suffering from mobility problems, disability and/or multi-morbidity [ 22 ]; however, more original studies have been reported in the following decade, making it necessary to update the synthetic evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Data from UK cohort study showed that active participants had a lower risk of frailty compared with inactive participants (43). Borda et al also reported that PA was significantly associated with a lower risk of developing frailty in the Mexican Health and Aging Study cohort (44). Based on mobile healthcare and wearable technologies, Li et al found that for 1 SD decrease in the temporal activity (more random activity fluctuations) correlations the risk of frailty increased by 31%; the risk of disability increased by 15-25%; and the risk of death increased by 26% (45).…”
Section: Discussionmentioning
confidence: 96%
“…Ageing does not inevitably lead to frailty; however, frailty usually intensifies with advancing age [ 1 , 2 , 3 ]. Other determinants of frailty have also been identified, including genetics, consequences of acute or traumatic pathologies, and unhealthy lifestyles [ 4 , 5 ]. These determinants can be potentiated by inflammatory and immunological mechanisms, leading to the appearance of typical frailty symptoms, with subsequent adverse results, such as falls, disability, and dependence [ 6 ].…”
Section: Introductionmentioning
confidence: 99%